Exploring Job Stress and Satisfaction among Probation Officers - Fathoni, Achmad Robbi (Fakultas Psikologi Universitas YARSI, 2025)
This study examines the relationship between job stress and job satisfaction among Probation Officers. This research is based on field observations, particularly at Bapas Class I Tangerang. Although most employees do not explicitly report any issues, they often work overtime beyond regular hours, indicating that stress might be a factor affecting their job satisfaction. Bapas Class I Tangerang has unique characteristics as a correctional institution dealing with high-risk situations, including managing inmates with serious criminal backgrounds and children involved in legal issues, which affects job stress levels among its employees. Using a quantitative correlational design, this study aims to investigate the relationship between job stress and job satisfaction among probation officers. The study sample consists of 31 Probation Officers selected purposively. The results revealed a significant negative correlation between job stress and job satisfaction (r = -.392, p<.01), with an R-Squared value of .154. These findings highlight the relationship between job stress and job satisfaction, where higher levels of job stress are associated with lower levels of job satisfaction among probation officers.